Study of streptomycin‑induced ototoxicity: protocol for a longitudinal study (2016)
Hearing impairment is due to various causes including ototoxicity from aminoglycosides. The susceptibility to aminoglycosides increases in the presence of certain mitochondria gene mutations. There is unrestrained use of aminoglycosides in many developing nations which may worsen the burden of hearing impairment in these countries but there is lack of data to drive required policy changes. Streptomycin (an aminoglycoside) is part of the drug regimen in re-treatment of tuberculosis. Exploring the impact of streptomycin ototoxicity in tuberculosis patients provides a unique opportunity to study aminoglycoside ototoxicity within the population thus providing data that can inform policy. Also, since streptomycin ototoxicity could adversely affect treatment adherence in tuberculosis patients this study could enable better pre-treatment counseling with subsequent better treatment adherence. Patients on tuberculosis re-treatment will be recruited longitudinally from Direct Observation Therapy-Short course centers. A baseline full audiologic assessment will be done before commencement of treatment and after completion of treatment. Early detection of ototoxicity will be determined using the American Speech and Hearing Association criteria and genetic analysis to determine relevant mitochondria gene mutations will be done. The incidence of ototoxicity in the cohort will be analyzed. Both Kaplan–Meier survival curve and Cox proportional hazards tests will be utilized to determine factors associated with development of ototoxicity and to examine association between genotype status and ototoxicity. This study will provide data on the burden and associated predictors of developing aminoglycoside induced ototoxicity. This will inform public health strategies to regulate aminoglycoside usage and optimization of treatment adherence and the management of drug-induced ototoxicity among TB patients. Furthermore the study will describe mitochondrial gene mutations associated with ototoxicity in the African population